2019
DOI: 10.1108/jhr-02-2019-0033
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the mechanisms of theory of planned behavior on Cyberbullying among Thai adolescents

Abstract: Purpose The purpose of this paper is to examine the etiological model of cyberbullying behaviors among Thai adolescents, testing the hypothesis that the constructs of theory of planned behavior (TPB), including self-esteem, will influence and have impact on cyberbullying intention and behaviors. Design/methodology/approach Structural equation modeling (SEM) was used to analyze the data. Self-administered questionnaires were used among multi-stage stratified random samples from secondary schools in the Bangko… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 28 publications
1
15
0
Order By: Relevance
“…Furthermore, cyberbullying intentions are likely a key mediator that could be integrated into BGCM. Several studies have shown that cyberbullying attitudes and behavior both correlate significantly with cyberbullying intentions (e.g., Heirman and Walrave, 2012 ; Pabian and Vandebosch, 2014 ; Auemaneekul et al, 2019 ).…”
Section: Cyberbullying Theory and Interventionsmentioning
confidence: 99%
“…Furthermore, cyberbullying intentions are likely a key mediator that could be integrated into BGCM. Several studies have shown that cyberbullying attitudes and behavior both correlate significantly with cyberbullying intentions (e.g., Heirman and Walrave, 2012 ; Pabian and Vandebosch, 2014 ; Auemaneekul et al, 2019 ).…”
Section: Cyberbullying Theory and Interventionsmentioning
confidence: 99%
“…The behavior of users in the network has a major impact on the development of cyberbullying, so that this does not happen, the family structure is very determinant in this aspect to raise self-esteem, play a leading role and users do not easily descend into intimidation. This should include activities that raise the self-esteem of their leaders and can be managed in an efficient and appropriate manner [11].…”
Section: Methodsmentioning
confidence: 99%
“…Cyberbullying is a type of violence in which people who commit bullying cannot be detected, or whether it is an act of an individual or a group of individuals cannot be determined [11]. Online social networks provide offenders with tools for aggressive actions and networks for committing misconduct.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Sittichai and Smith [ 36 ] reported a review of studies on bullying and cyberbullying in South-East Asian countries, including Thailand, before and up to 2014. Since 2014 studies of cyberbullying in Thailand among school students include [ 4 , 37 , 38 ], and [ 39 , 40 ] among university students. These studies have documented a variety of cyberbullying behaviors, and an appreciable incidence of the phenomenon, with actual incidence levels depending on the definitions and criteria.…”
Section: Introductionmentioning
confidence: 99%